Incidence and predictors of cardiovascular disease mortality and all-cause mortality in patients with type II diabetes with peripheral arterial disease. - Amaraporn Rerkasem; Ampica Mangklabruks; Supawan Buranapin; Kiran Sony; Nimit Inpankaew; Rath Rerkasem; Sasinat Pongtam; Kochaphan Phirom; Kittipan Rerkasem (PLoS ONE)
Objective This cohort study estimated the incidence and predictors of cardiovascular disease (CVD) and all-cause mortality among patients with type 2 diabetes mellitus (T2DM) and various stages of peripheral arterial disease (PAD) at the largest tertiary referral hospitals in upper-northern Thailand. Methods This study recruited 278 T2DM and PAD patients for a 7-year cohort study. These patients completed health questionnaires and underwent physical examinations including ankle-brachial index measurements and clinical assessment to determine PAD severity. Mortality endpoints were determined using hospital death registers and national death records. The Cox proportional hazards and subdistribution hazard models were used to estimate PAD's effect on mortality, quantifying the association with hazard ratios (HR) and subdistribution hazard ratios (SHR). Results PAD patients were categorized into three subgroups. Over seven years, the cumulative all-cause mortality rate was 36%, or 6.4 deaths per 100 person-years. Multivariable analysis revealed critical limb ischemia (CLI) patients had significantly higher risks of all-cause (HR 5.26, 95%CI 3.10-8.94) and CVD mortality (SHR 6.20, 95%CI 3.20-12.03) compared to their asymptomatic peers. No statistically significant differences in non-CVD mortality were noted across PAD subgroups. Conclusion CLI, chronic kidney disease, and underweight (body mass index < 18.5 kg/m2) emerged as independent mortality predictors. Conversely, asymptomatic PAD patients had a similar overall mortality risk as those with intermittent claudication. These findings highlight the need for risk stratification and patient empowerment to optimize management of these complex conditions.